Reduced graphene oxide composite material, preparation method thereof and application of reduced graphene oxide composite material in enrichment and detection of alkylphenol

Through the magnetic dispersion solid-phase extraction and UPLC-MS analysis technology of Fe3O4@rGO@poly3-aminophenol composite material, the problem of detection of alkylphenol residues in bean sprouts is solved, and a fast, sensitive and repeatable detection effect is achieved. Ensure food safety.

CN119186518APending Publication Date: 2024-12-27HUNAN AGRI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411383743.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately detect the content of alkylphenol residues in bean sprouts, especially BPA, OP and NP, and lacks sensitive and repeatable detection methods.

Method used

Fe3O4@rGO@poly3-aminophenol composite material is used as solid-phase microextraction adsorbent, and the enrichment and detection of alkyl phenols are achieved through magnetic dispersed solid-phase extraction and UPLC-MS analysis technology. The composite material is loaded with Fe3O4 nanoparticles and poly3-aminophenol from reduced graphene oxide (rGO) carrier, and uses its large specific surface area and strong affinity for adsorption and extraction.

Benefits of technology

It realizes rapid, sensitive and repeatable detection of BPA, OP and NP in bean sprouts, providing high sensitivity and high accuracy analysis results, ensuring food safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005070528970000121
    Figure BDA0005070528970000121
  • Figure BDA0005070528970000131
    Figure BDA0005070528970000131
  • Figure BDA0005070528970000132
    Figure BDA0005070528970000132
Patent Text Reader

Abstract

The invention relates to the technical field of analytical chemistry and biological detection, in particular to a reduced graphene oxide composite material, a preparation method of the reduced graphene oxide composite material and application of the reduced graphene oxide composite material in enrichment and detection of alkylphenol. The reduced graphene oxide composite material is Fe3O4 (at) rGO (at) poly (3-aminophenol), rGO is used as a carrier, and Fe3O4 and poly (3-aminophenol) are loaded on the surface of rGO. The reduced graphene oxide composite material can be used as a solid phase microextraction adsorbent, and is used for detecting the content of bisphenol A (BPA (bisphenol A)), the content of octylphenol (OP (octylphenol)) and the content of nonylphenol (NP (nonylphenol)) in bean sprouts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of analytical chemistry and biological detection, and in particular to a reduced graphene oxide composite material and a preparation method thereof, and application of the composite material in the enrichment and detection of alkylphenols. Background Art

[0002] In recent decades, pollutants in the environment, especially alkylphenol residues, have attracted widespread attention. These alkylphenols have been detected in various sources including vegetables, vegetable hydroponic equipment and food packaging materials. Bisphenol A (BPA), octylphenol (OP) and nonylphenol (NP) are the most common alkylphenol contaminants in food. Alkylphenol residues have certain estrogenic activity and their accumulation in the food chain poses a significant risk to human health. There is great concern about the monitoring of alkylphenol residue levels to prevent them from exceeding the permitted limits. Therefore, it is necessary to develop a convenient and accurate detection method for smooth and effective monitoring.

[0003] Bean sprouts are mainly cultivated in plastic hydroponic boxes and are usually packed in plastic bags during storage and transportation. This increases the possibility of alkylphenols migrating from contaminated water, plastic hydroponic containers and plastic packaging into bean sprouts. However, there are no reports on the presence of alkylphenol residues in bean sprouts. This highlights the urgent need to develop an accurate, convenient and sensitive method to monitor alkylphenol residues in bean sprouts and bean sprout products.

[0004] In recent years, magnetic dispersion solid phase extraction (MD-SPE) has been used for the quantification of trace alkylphenols. It is a method worth considering to analyze the alkylphenol content in vegetable samples by utilizing the high selectivity provided by MD-SPE and the ability of functionally modified nanoadsorbents. Various types of carbon-based materials have been reported to enrich alkylphenols. In addition, the highly sensitive UPLC-MS analysis technology is an ideal choice for determining the content of very low concentrations of alkylphenols in complex vegetable matrices. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a reduced graphene oxide (rGO) composite material and a preparation method thereof. The rGO composite material of the present invention can be used as a solid phase microextraction adsorbent for enriching and extracting alkylphenols. Based on this application, the present invention also provides a method for detecting the content of BPA, OP and NP in bean sprouts using the rGO composite material, which is rapid, sensitive and repeatable.

[0006] In one aspect of the present invention, a rGO composite material is provided, wherein the rGO composite material is Fe3O4@rGO@poly 3-aminophenol, wherein the Fe3O4@rGO@poly 3-aminophenol uses rGO as a carrier, and the surface of the rGO is loaded with Fe3O4 and poly 3-aminophenol.

[0007] The Fe3O4@rGO@poly 3-aminophenol composite material of the present invention is a particle-modified folded sheet structure, specifically, the particles are anchored on the folded sheet structure. The folded sheet structure is used as a carrier, which is rGO, specifically a wrinkled wavy graphene structure; the particles include Fe3O4 nanoparticles and PmAP nanoparticles, which are uniformly dispersed (coexist) on the carrier.

[0008] Fe3O4 can allow nanomaterials to quickly achieve magnetic separation in pretreatment, and spherical Fe3O4 can also increase the surface porosity of nanomaterials; rGO has a large specific surface area and has a good adsorption efficiency for alkylphenols. Poly(3-aminophenol) has a strong affinity for the target alkylphenol compounds because of its large aromatic domain, which is conducive to van der Waals forces and other non-covalent interactions, and poly(3-aminophenol) can provide more "gap space", which is more conducive to capturing the target alkylphenol. In addition, the Fe3O4@rGO@poly(3-aminophenol) composite material of the present invention has a rough surface and obvious gaps, providing multiple adsorption sites for alkylphenols.

[0009] According to some embodiments of the present invention, the specific surface area of ​​the rGO composite material is 15 to 25 m 2 / g, for example 20-25m 2 / g.

[0010] In another aspect, the present invention provides a method for preparing a rGO composite material, comprising the following steps:

[0011] Adding divalent iron salt and trivalent iron salt to the dispersion of rGO to obtain a mixed solution, heating the mixture in the presence of ammonia water to obtain Fe3O4@rGO; polymerizing 3-aminophenol with a first initiator to obtain poly 3-aminophenol; mixing the Fe3O4@rGO and the poly 3-aminophenol, adding a second initiator, stirring, and obtaining the mixture.

[0012] According to some embodiments of the present invention, the divalent iron salt is selected from at least one of ferrous chloride, ferrous sulfate, ferrous nitrate, or a hydrate thereof, such as a tetrahydrate or a hexahydrate.

[0013] According to some embodiments of the present invention, the ferric iron salt is selected from at least one of ferric chloride, ferric sulfate, ferric nitrate, or a hydrate thereof, such as a tetrahydrate or a hexahydrate.

[0014] According to some embodiments of the present invention, the molar ratio of the divalent iron salt to the trivalent iron salt is 1:1.5-3, for example, 1:1.5-2.5, or about 1:2.

[0015] According to some embodiments of the present invention, the concentration of rGO in the mixed solution is 0.5-1.5 mg / mL, for example, 0.5-1.2 mg / mL, 0.5-1.0 mg / mL, 0.5-0.8 mg / mL, 0.6-1.5 mg / mL, 0.6-1.2 mg / mL, 0.6-1.0 mg / mL, 0.6-0.8 mg / mL, 0.7-1.0 mg / mL, 0.7-0.9 mg / mL, or about 0.8 mg / mL.

[0016] According to some embodiments of the invention, the concentration of the divalent iron salt in the mixed solution is 2 to 10 mg / mL, for example, 2 to 8 mg / mL, 2 to 6 mg / mL, 3 to 10 mg / mL, 3 to 8 mg / mL, 3 to 6 mg / mL, 4 to 10 mg / mL, 4 to 8 mg / mL, 4 to 6 mg / mL, 5 to 7 mg / mL, about 6 mg / mL.

[0017] According to some embodiments of the invention, the concentration of the ferric iron salt in the mixed solution is 8-30 mg / mL, for example, 8-24 mg / mL, 8-20 mg / mL, 8-18 mg / mL, 10-30 mg / mL, 10-25 mg / mL, 10-20 mg / mL, 10-18 mg / mL, 12-30 mg / mL, 12-24 mg / mL, 12-20 mg / mL, 12-18 mg / mL, 15-30 mg / mL, 15-25 mg / mL, 15-20 mg / mL, 15-18 mg / mL, or about 16 mg / mL.

[0018] According to some embodiments of the present invention, the mass ratio of the rGO to the ferric salt is 1:10-40, for example, 1:10-35, 1:10-30, 1:10-25, 1:10-20, 1:15-35, 1:15-30, 1:15-25, 1:15-20, 1:20-30, 1:20-25, or about 1:20.

[0019] According to some embodiments of the present invention, the mass ratio of the rGO to the divalent iron salt is 1:3-15, for example, 1:3-12, 1:3-10, 1:3-9, 1:3-8, 1:4-12, 1:4-10, 1:4-9, 1:4-8, 1:5-10, 1:5-9, 1:5-8, 1:6-9, 1:6-8, 1:7-8, or about 1:7.5.

[0020] According to some embodiments of the present invention, the divalent iron salt and the trivalent iron salt are added dropwise to the dispersion of rGO.

[0021] According to some embodiments of the present invention, the mixed solution is in a uniform state. The present invention does not impose any particular limitation on the method for making the mixed solution uniform, for example, stirring or ultrasound may be used. Preferably, the mixed solution is stirred for 30 to 90 minutes until it is in a uniform state.

[0022] According to some embodiments of the present invention, the concentration of the ammonia water is 25-30 wt %, and the volume ratio of the ammonia water to the mixed liquid is 1:3-6 mL, for example, 1:3-5 mL, 1:4-6 mL, 1:4-5 mL, 1:5-6 mL.

[0023] According to some embodiments of the present invention, the temperature of the heating reaction is 70 to 100° C., such as 70 to 90° C., and / or the time of the heating reaction is 20 to 50 minutes.

[0024] According to some embodiments of the present invention, after the heating reaction is completed, the Fe3O4@rGO is washed with distilled water and then dried, wherein the drying temperature is 60 to 80°C and the drying time is 1 to 4 hours.

[0025] According to some embodiments of the present invention, the first initiator is selected from at least one of ammonium persulfate, sodium persulfate, and potassium persulfate.

[0026] According to some embodiments of the present invention, the molar ratio of 3-aminophenol to the first initiator is 1:0.05-2, for example, 1:0.05-1.5, 1:0.05-1.2, 1:0.5-1.8, 1:0.5-1.5, 1:0.5-1.2, 1:0.8-1.5, 1:0.8-1.2, 1:1-1.5, 1:1-1.2.

[0027] According to some embodiments of the present invention, the polymerization reaction temperature is -4°C to 4°C, and the reaction system of the polymerization reaction changes from a colorless solution to a dark brown suspension, indicating that the polymerization reaction is completed. For example, the polymerization reaction time is 4 to 12 hours, such as 6 to 10 hours.

[0028] According to some embodiments of the present invention, 3-aminophenol is dissolved in a sodium acetate solution, and then the first initiator solution is added to cause the polymerization reaction to obtain poly-3-aminophenol.

[0029] According to some embodiments of the present invention, the molar ratio of 3-aminophenol to sodium acetate is 1:0.8-1.5, for example, 1:0.8-1.2, 1:0.8-1.1, 1:0.8-1.0, 1:0.9-1.5, 1:0.9-1.2.

[0030] According to some embodiments of the present invention, the concentration of the sodium acetate solution is 0.05 to 2 mol / L.

[0031] According to some embodiments of the present invention, the concentration of the first initiator solution is 0.2-0.4 mol / L.

[0032] According to some embodiments of the present invention, after the polymerization reaction is completed, the poly 3-aminophenol is washed with water and then dried, wherein the drying temperature is 40 to 60° C. and the drying time is 8 to 16 hours.

[0033] According to some embodiments of the present invention, the second initiator is selected from at least one of ammonium persulfate, sodium persulfate, and potassium persulfate.

[0034] The mass ratio of the Fe3O4@rGO to the poly 3-aminophenol is 1:20-60, for example, 1:20-50, 1:20-40, 1:30-60, 1:30-50, 1:30-40, 1:40-60, 1:40-50, or about 1:40.

[0035] The mass ratio of the Fe3O4@rGO to the second initiator is 1:100-400, for example, 1:100-350, 1:100-300, 1:100-250, 1:150-350, 1:150-300, 1:150-250, 1:200-300, 1:200-250.

[0036] According to some embodiments of the present invention, the stirring temperature is -4°C to 4°C, and the stirring time is 4 to 12 hours, such as 6 to 10 hours.

[0037] According to some embodiments of the present invention, the poly 3-aminophenol and sodium acetate are dissolved in water, subjected to a first ultrasound treatment, the Fe3O4@rGO is added, subjected to a second ultrasound treatment, the second initiator solution is added dropwise, and stirred to obtain the rGO composite material.

[0038] According to some embodiments of the present invention, the mass ratio of Fe3O4@rGO to sodium acetate is 1:10-40, for example, 1:10-30, 1:10-25, 1:10-20, 1:15-30, 1:15-25, 1:15-20, 1:20-25, or about 1:20.

[0039] According to some embodiments of the present invention, the mass volume ratio of the Fe3O4@rGO to water is 1 mg: 10-20 mL.

[0040] According to some embodiments of the present invention, the concentration of the second initiator solution is 0.2-0.4 mol / L.

[0041] The present invention does not particularly limit the temperature, power and time of the two ultrasonic treatments, as long as uniform mixing of the components is achieved. For example, the first ultrasonic treatment can be performed at room temperature (20°C to 30°C), and the second ultrasonic treatment can be performed in an ice bath (-4°C to 4°C); the power of the two ultrasonic treatments can be 10 to 30 kHz respectively; and the time of the two ultrasonic treatments can be 20 to 40 minutes respectively.

[0042] According to some embodiments of the present invention, after the stirring is completed, the rGO composite material is washed with deionized water and / or methanol and then dried, wherein the drying temperature is 100-150° C. and the drying time is 8-16 hours.

[0043] In another aspect, the present invention provides a device for enriching and detecting alkylphenols, comprising the above-mentioned rGO composite material.

[0044] According to some embodiments of the present invention, the rGO composite material can be used as a material for a solid phase microextraction probe in the device or as a filler for a solid phase extraction column.

[0045] Another aspect of the present invention provides the use of the above rGO composite material in the enrichment and detection of alkylphenols.

[0046] According to some embodiments of the present invention, the alkylphenol is selected from at least one of BPA, OP and NP.

[0047] According to some embodiments of the present invention, the objects of enrichment and detection are vegetable samples, for example, bean sprouts, including mung bean sprouts, soybean sprouts, peanut sprouts, cabbage, and radish.

[0048] In another aspect, the present invention provides a method for detecting alkylphenols in bean sprouts, comprising sequentially performing sample treatment and solid phase microextraction on a bean sprout sample, and then performing liquid chromatography tandem mass spectrometry detection on a test solution obtained after solid phase microextraction to determine the alkylphenols in the bean sprout sample;

[0049] The sample processing comprises mixing the bean sprout sample, the internal standard and acetone for extraction to obtain an extract;

[0050] The solid phase microextraction comprises oscillating and extracting the extract with the rGO composite material to obtain the rGO composite material adsorbed with alkylphenol, and then oscillating and desorbing the alkylphenol adsorbed on the rGO composite material.

[0051] According to some embodiments of the present invention, the alkylphenol is selected from at least one of BPA, OP and NP.

[0052] According to some embodiments of the present invention, the internal standard can be selected from deuterium-labeled alkylphenols, such as deuterium-labeled BPA, deuterium-labeled OP or deuterium-labeled NP. In the present invention, the internal standard is preferably BPA-d16 for cost considerations.

[0053] According to some embodiments of the present invention, the bean sprout sample is stored at -20°C.

[0054] According to some embodiments of the present invention, the sample processing further includes a pretreatment step, and the pretreatment step includes grinding the fresh sprouts with liquid nitrogen.

[0055] According to some embodiments of the present invention, the mass volume ratio of the bean sprout sample to acetone is 1g:5-15mL, for example, 1g:5-12mL, 1g:5-10mL, 1g:8-12mL, about 1g:10mL.

[0056] According to some embodiments of the present invention, the mass ratio of the bean sprout sample to the internal standard is 1 g: 0.01-1 μg.

[0057] According to some embodiments of the present invention, during the sample processing, the mixing includes mixing the bean sprout sample with an internal standard, and then adding acetone after 20 to 40 minutes.

[0058] According to some embodiments of the present invention, during the sample processing, the extraction is performed under ultrasonic conditions (power 10-30 kHz, temperature 10-35° C.) for 20-40 min.

[0059] According to some embodiments of the present invention, the mass ratio of the bean sprout sample to the rGO composite material is 1g:1-10mg, for example, 1g:2-9mg, 1g:3-8mg, 1g:3-6mg, 1g:3-5mg, 1g:4-9mg, 1g:4-8mg, 1g:4-6mg, 1g:4-5mg, 1g:5-6mg, and about 1g:5mg.

[0060] According to some embodiments of the present invention, the oscillation extraction time is 20 to 40 minutes.

[0061] Since the rGO composite material of the present invention has magnetism, after the oscillation extraction, the rGO composite material adsorbed with alkylphenol can be obtained by magnetic separation.

[0062] According to some embodiments of the present invention, ethyl acetate is used for the oscillation desorption, wherein the mass volume ratio of the rGO composite material to ethyl acetate is 1 mg: 5 to 20 μL, for example, 1 mg: 5 to 15 μL, 1 mg: 5 to 12 μL, 1 mg: 5 to 10 μL, 1 mg: 6 to 15 μL, 1 mg: 6 to 12 μL, 1 mg: 6 to 10 μL, 1 mg: 8 to 12 μL, 1 mg: 8 to 10 μL, or about 1 mg: 10 μL.

[0063] According to some embodiments of the present invention, the oscillation desorption time is 20 to 40 minutes.

[0064] According to some embodiments of the present invention, the desorption liquid obtained after solid phase extraction is concentrated and redissolved in methanol to obtain the test solution; wherein the mass volume ratio of the rGO composite material to methanol is 1 mg: 20-60 μL.

[0065] According to some embodiments of the present invention, the liquid chromatography conditions of the liquid chromatography tandem mass spectrometry method include:

[0066] Chromatographic column: Agilent ZORBAX SB-C18 chromatographic column, preferably, with specifications of 2.1*100mm, 1.8μm;

[0067] Mobile phase A: 0.05-0.2% ammonia water;

[0068] Mobile phase B: acetonitrile;

[0069] Elution method: gradient elution;

[0070] The procedure of the gradient elution is:

[0071] 0-2 minutes, the volume fraction of mobile phase B is maintained at 55-65%,

[0072] 2-3 minutes, the volume fraction of mobile phase B increases from 55-65% to 75-85%,

[0073] 3-5 minutes, the volume fraction of mobile phase B is maintained at 75-85%,

[0074] 5-8 minutes, the volume fraction of mobile phase B decreased from 75-85% to 55-65%;

[0075] Flow rate: 0.1~1mL / min;

[0076] Column temperature: 30-45°C;

[0077] Injection volume: 1~10μL.

[0078] According to some preferred embodiments of the present invention, the mobile phase A is aqueous ammonia with a mass concentration of 0.05-0.15%.

[0079] According to some preferred embodiments of the present invention, the procedure of the gradient elution is:

[0080] 0-2 minutes, the volume fraction of mobile phase B is maintained at 58-62%,

[0081] In 2-3 minutes, the volume fraction of mobile phase B increases from 58-62% to 78-82%.

[0082] 3-5 minutes, the volume fraction of mobile phase B is maintained at 78-82%,

[0083] In 5-8 minutes, the volume fraction of mobile phase B decreased from 78-82% to 58-62%.

[0084] According to some more preferred embodiments of the present invention, the procedure of the gradient elution is:

[0085] 0-2 minutes, the volume fraction of mobile phase B is maintained at 60%,

[0086] 2-3 minutes, the volume fraction of mobile phase B increased from 60% to 80%,

[0087] 3-5 minutes, the volume fraction of mobile phase B is maintained at 80%,

[0088] During 5-8 minutes, the volume fraction of mobile phase B decreased from 80% to 60%.

[0089] According to some preferred embodiments of the present invention, the mass spectrometry conditions of the liquid chromatography tandem mass spectrometry method include:

[0090] Combined with a triple quadrupole / linear ion trap mass spectrometer;

[0091] Ion source: electrospray ESI ion source;

[0092] Nebulizer gas flow rate: 7.5~8.5L / min;

[0093] The mass spectrometer source temperature is 280-320°C;

[0094] Atomizer pressure is 40-60 psi;

[0095] Capillary voltage is 3200~3800V;

[0096] Scanning mode: negative ionization mode;

[0097] Detection method: multiple reaction monitoring (MRM) mode;

[0098] Drying gas and collision gas: nitrogen;

[0099] According to some embodiments of the present invention, the following beneficial effects are achieved:

[0100] The present invention obtains a rGO composite material, which has a strong adsorption effect on alkylphenols and can be used as a solid phase microextraction adsorbent. Based on this, the present invention also establishes a rapid, sensitive and repeatable analytical technique for detecting the content of residual BPA, OP and NP in bean sprouts.

[0101] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0102] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0103] Figure 1 is the XRD spectrum of the material prepared in Example 1 of the present invention;

[0104] Figure 2 is the FI-TR diagram of the material prepared in Example 1 of the present invention;

[0105] Figure 3 is a BET diagram of the specific surface area of ​​the material obtained in Example 1 of the present invention;

[0106] Figure 4 is the SEM image of rGO, Fe3O4@rGO, and Fe3O4@rGO@PmAP in Example 1 of the present invention;

[0107] Figure 5 is the TEM image of rGO, Fe3O4@rGO, and Fe3O4@rGO@PmAP in Example 1 of the present invention;

[0108] Figure 6 is the Pareto chart of the standardized (P<0.05) significant effects of BPA, OP and NP by Plackett-Burman design (n=2);

[0109] Figure 7 It is the result graph of the effect of adsorbent dosage on the extraction efficiency of target BPA, OP, and NP;

[0110] Figure 8 This is the test result of alkylphenols in three kinds of bean sprouts: mung bean sprouts, soybean sprouts and peanut sprouts. DETAILED DESCRIPTION

[0111] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0112] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0113] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0114] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±5%.

[0115] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0116] Alkylphenol residues in vegetables may pose a potential food safety risk to humans, but there are no reports on alkylphenol residues in bean sprouts. In this paper, a method for detecting alkylphenol residues in bean sprouts using magnetic dispersion solid phase extraction (MD-SPE)-ultra-performance liquid chromatography-tandem MS (UPLC-MS / MS) was established. Fe3O4@rGO@poly(3-aminophenol) composites were synthesized for the first time and used as an effective adsorbent for magnetic dispersion solid phase extraction of alkylphenols. The magnetic composites were characterized using X-ray powder scattering, Fourier transform infrared spectroscopy, scanning electron microscopy, and transmission electron microscopy. To optimize the extraction process, Plackett-Burman factor design was used to fine-tune multiple parameters of MD-SPE. In addition, the sensitivity of UPLC-MS / MS enabled the alkylphenols in bean sprout samples to be accurately quantified. The analytical method produced high linearity (R 2>0.9989) and recoveries (90.4% to 108.5%). Minimal matrix effects (7.5% to 12.4%), impressive limits of detection (0.89 to 13.62 μg / mL), and reliable reproducibility (intraday: 2.0% to 13.5%; interday: 0.7% to 11.6%) were achieved. Therefore, the method of the present invention can be successfully used to analyze alkylphenol residues in vegetable samples, making it a reliable tool for ensuring food safety.

[0117] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0118] The general technical means in the art can be adopted to adopt the improved Hummer method to add hydrazine hydrate to the graphene solution under condensation conditions to obtain rGO.

[0119] (1) Single standard stock solution:

[0120] 4-tert-octylphenol standard (purity>99.5%), nonylphenol standard (purity>99.0%), bisphenol A standard (purity>98.5%), BPA-d16 standard (deuterium-labeled bisphenol A, purity>98%), among which BPA-d16 was used as internal standard (IS), all the above standards were purchased from Aladdin (Shanghai, China). Methanol was used as solvent, and single standard stock solutions of 4-tert-octylphenol, nonylphenol, bisphenol A and internal standard were prepared at 1000 mg / L and stored in the dark at -20°C.

[0121] (2) Standard working solution:

[0122] Use a pipette to accurately transfer 10 μL of each 1000 mg / L single standard stock solution into a brown volumetric flask, use methanol as the solvent, dilute to 10 mL, and obtain a mixed standard dilution with a concentration of 1 mg / L. Prepare mixed standard working solutions of different concentrations, with concentrations of 1, 5, 10, 50, 100, and 200 μg / L. Draw a standard working curve and prepare it as needed.

[0123] (3) Internal standard solution:

[0124] Accurately weigh 10 mg of BPA-d16 into a 10 mL volumetric flask, dilute with methanol to prepare an internal standard stock solution with a concentration of 1000 mg / L. Then dilute it with methanol to an internal standard dilution solution of 1 mg / L. Before each measurement, transfer 100 μL to the bean sprout sample to correct for losses and matrix interference during pretreatment and measurement.

[0125] Example 1

[0126] This embodiment provides a reduced graphene oxide composite material, specifically a Fe3O4@rGO@PmAP composite material.

[0127] 1. The preparation steps of the reduced graphene oxide composite material are as follows:

[0128] Synthesis of S1 and Fe3O4@rGO

[0129] With the help of a magnetic stirrer, 40 mg of rGO was dispersed in ultrapure water, and 800 mg of FeCl3·6H2O and 300 mg of FeCl were added dropwise. 2· 4H2O to form 50mL rGO dispersion. Continue magnetic stirring for 60 minutes to obtain a uniform solution. The temperature was raised to 80°C, and 10mL of aqueous ammonia (chromatographic grade, about 25% to 28% in H2O) was added to the mixed solution. The resulting solution was stirred for another 30 minutes to obtain a hydrogel-like substance. Subsequently, the hydrogel-like substance was washed with distilled water and placed in a vacuum drying oven (YGM-DZR, China) at about 70°C for 2 hours, and finally the Fe3O4@rGO was collected using a magnetic field.

[0130] S2. Synthesis of poly 3-aminophenol (PmAP)

[0131] 260 mg of 3-aminophenol (3-mAP) was dissolved in 25 mL of 0.1 M sodium acetate solution. The resulting solution was placed in an ice bath and 10 mL of 0.25 M ammonium persulfate solution was added. After vigorous stirring for 8 hours, the reaction system changed from a colorless solution to a dark brown suspension. The suspension was centrifuged and the precipitate was washed with water five times to remove unreacted monomers and other water-soluble components. Finally, the resulting precipitate was separated and dried in a drying oven at 45 ° C for 10 hours to obtain poly 3-aminophenol for the next step of material synthesis.

[0132] Synthesis of S3, Fe3O4@rGO@poly-3-aminophenol

[0133] 200 mg of PmAP and 100 mg of anhydrous sodium acetate powder were dissolved in 80 mL of deionized water and then sonicated in an ultrasonic bath at 20 kHz for 30 min. 5 mg of Fe3O4@rGO powder prepared in step S1 was added to the solution and then sonicated in an ice bath at 20 kHz for 30 min to fully mix the raw materials. After that, 20 mL of 0.25 M ammonium persulfate solution (prepared by dissolving 1141.4 mg of ammonium persulfate powder in 20 mL of deionized water) was added dropwise to the reaction solution. The mixed solution was vigorously stirred for 8 hours under 0 ° C ice bath conditions, and then washed with deionized water and methanol and centrifuged several times. The sediment was collected and dried in a vacuum oven at 120 ° C for 10 hours. The dried precipitate was then cooled to room temperature and ground in an agate mortar to obtain a composite of Fe3O4@rGO and PmAP, i.e., Fe3O4@rGO@PmAP powder.

[0134] 2. Characterization of Fe3O4@rGO@PmAP composites

[0135] Figure 1 The X-ray diffraction (XRD) pattern of the prepared Fe3O4@rGO@PmAP composite material is shown. The characteristic diffraction peak of Fe3O4 is very consistent with the standard XRD data of magnetite. After Fe3O4@rGO is grafted with PmAP, the peak position in the spectrum does not change, indicating that the grafted PmAP has no effect on the crystal structure of Fe3O4 nanoparticles. PmAP does not show sharp crystal diffraction peaks in the spectrum. Although a broad peak appears at 2θ=20-30, the diffraction peak intensity gradually decays and tends to be flat, indicating that the PmAP state is amorphous. Figure 2 It shows that the FT-IR of the composite material is at 3436cm -1 A relatively strong peak was detected at 1510 cm -1 The weaker absorption band at 1614 cm is the NH bending vibration peak, indicating the presence of an amide bond. -1 The absorption band at 585cm indicates the presence of C=O vibration, which should be the stretching vibration of PmAP. -1 The typical absorption band at is attributed to Fe-O-Fe vibration, which means that it is loaded with Fe3O4. The N2 adsorption-desorption isotherm of Fe3O4@rGO@PmAP composite material ( Figure 3 ) refers to type IV hysteresis loop (IUPAC). The specific surface area of ​​the composite material was calculated by BET analysis to be 21.09 m 2 / g.

[0136] The Fe3O4@rGO@PmAP nanocomposites were characterized using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 4) can be observed that the particles are roughly anchored on the folded sheet structure. TEM image ( Figure 5 ) further confirmed that the nanoparticles were dispersed on the wrinkled wavy graphene structure. In summary, these results indicate that the product is as expected, and Fe3O4 and PmAP nanoparticles coexist uniformly on rGO sheets. In addition, the rough surface and obvious gaps of the composite provide multiple adsorption sites for the target alkylphenols.

[0137] Example 2

[0138] This embodiment provides a device for enriching and detecting alkylphenols, wherein the solid phase microextraction probe material or solid phase extraction column filler includes the Fe3O4@rGO@PmAP composite material prepared in Example 1. The device is particularly suitable for enriching and detecting alkylphenols (e.g., 4-tert-octylphenol, nonylphenol, bisphenol A) in vegetable samples (e.g., mung bean sprouts, soybean sprouts, peanut sprouts, cabbage and radish).

[0139] Example 3

[0140] This embodiment provides a method for enriching and detecting alkylphenols using Fe3O4@rGO@PmAP composite materials.

[0141] Bean sprout samples were purchased from the local market, and all samples were collected and stored at −20 °C before analysis.

[0142] 1. Sample pre-treatment steps

[0143] Alkylphenols were extracted from sprout samples using a magnetic dispersive solid phase extraction (MD-SPE) method. Specifically, the steps include: weighing 1 g of sprout sample, grinding fresh sprouts with liquid nitrogen, and transferring the sprout powder to a centrifuge tube; adding 100 μL of 1 mg / L internal standard (BPA-d16) to the centrifuge tube and keeping it for 30 minutes; adding 10 mL of acetone as the extraction solvent, and vortexing the mixing tube. The extract was placed in an ultrasonic water bath at 20 kHz power for 30 minutes and the acetone layer was collected. Thereafter, 5 mg of the magnetic nanoparticles prepared in Example 1 were added, the centrifuge tube was shaken vigorously, and then adsorbed for 30 minutes. The nanoparticles were collected by magnetic separation, redispersed in 50 μL of desorption solution (ethyl acetate), desorbed for 30 minutes, the eluate was collected, evaporated, and the dried residue was redissolved in 200 μL of methanol for UPLC-MS / MS analysis.

[0144] 2. Detection conditions for UPLC-MS / MS analysis

[0145] Samples were analyzed using a Shimadzu Prominence LC-30AD (Shimadzu Corporation, Columbia, MD) coupled to an ABSciex5500QTRAP triple quadrupole / linear ion trap mass spectrometer. Data were acquired and analyzed using AB SciexAnalyst (version 1.5.1) and Library View, respectively. Negative ionization mode was used. Separation was performed using an Agilent ZORBAX SB-C18 column (mm×mm, inner diameter μm), with a mobile phase consisting of 0.1% ammonia (A) and acetonitrile (B) at a flow rate of 0.5 mL / min. The elution gradient program is as follows: 0-2 minutes, 60% B (i.e., the volume fraction of mobile phase B is maintained at 60%); 2-3 minutes, 60%-80% B (i.e., the volume fraction of mobile phase B is increased from 60% to 80%); 3-5 minutes, 80% B (i.e., the volume fraction of mobile phase B is maintained at 80%); 5-8 minutes, 80%-60% B (i.e., the volume fraction of mobile phase B is reduced from 80% to 60%). The column temperature is maintained at 40°C, and the injection volume is 5 μL.

[0146] The target compounds were quantitatively analyzed using the multiple reaction monitoring (MRM) mode shown in Table 1, where the drying gas and collision gas were nitrogen, the ionization source conditions were: nebulizer gas flow rate of 8 L / min, mass spectrometer source temperature of 300 °C, nebulizer pressure of 50 psi, and capillary voltage of 3500 V.

[0147] Table 1 Detailed information of target alkylphenols and their multiple reaction monitoring (MRM) parameters

[0148]

[0149]

[0150] 3. Optimizing Important Variables in SPME Process Using Plackett-Burman Screening

[0151] Plackett-Burman Design (PBD) can evaluate the impact of multiple parameters and identify important variables in a full factorial experiment. PBD can reduce costs by screening test parameters with as few experiments as possible. A two-stage PBD with 12 runs was used to screen for important variables affecting extraction efficiency.

[0152] Take bean sprouts as samples, add various standards, and screen according to the conditions under "II. Detection conditions of UPLC-MS / MS analysis".

[0153] According to preliminary experiments, the MD-SPE adsorbent dosage (m), extractant volume (V extract ), extraction time (T extract), adsorption time (T adsorbent ), elution time (T elution ) and elution volume (V elution ) and other variables. The details of the PB factorial design are shown in Table 2. The PB design was applied and the values ​​of the measured responses are recorded in Table 3.

[0154] Table 2 Plackett-Burman design for screening six variables in MD-SPE

[0155]

[0156] Table 3 Plackett-Burman design and results in the MD-SPE process

[0157]

[0158]

[0159] Figure 6 Pareto plots of six variables associated with MD-SPE are shown. All the variables studied had a positive impact on the extraction of alkylphenols from bean sprouts. The standardized Pareto plots of the significant variables for three alkylphenols are shown in the figure (P<0.05). The key parameters affecting the extraction of alkylphenols were >2.571 at 95% confidence level. In the present invention, the significant factor affecting the efficiency of extraction of 4-n-octylphenol, 4-n-nonylphenol and bisphenol A from bean sprout samples was adsorbent dosage (P<0.05). The extraction efficiency of solid phase microextraction can be affected by changing the amount of adsorbent used, while the non-significant variables were volume (10 mL), extraction time (30 minutes), adsorption time (30 minutes), elution time (30 minutes) and elution volume (100 μL).

[0160] 4. Optimization of important variables of adsorbent dosage

[0161] The optimal amount of adsorbent was determined by single factor experiments. As shown in the PB experiment. When the adsorbent dosage was between 1 and 5 mg, the adsorption efficiency increased with the increase of adsorbent dosage. However, when the adsorbent dosage exceeded 5 mg, the adsorption efficiency tended to stabilize. At the same time, the loss of GO in the extraction and clean-up steps was taken into account when selecting the dosage. At least 5 mg of GO was required to ensure that the adsorption was sufficient to offset the effect of the loss. Values ​​of 1, 3, 5, 7, and 10 mg were selected to obtain the best recovery. From the single factor experiment ( Figure 7 ) It can be seen that the best recovery was obtained when 5 mg of Fe3O4@rGO@PmAP composite was used, and the corresponding recovery range was 55% to 90%. Therefore, the adsorbent dosage for the next experiment was set to 5 mg.

[0162] V. Method Validation

[0163] The validation process focused on linearity, precision, limit of detection (LOD), and limit of quantification (LOQ), as shown in Table 4. A mixed standard solution (i.e., the standard working solution) was prepared, and the linearity of six increasing concentration levels (1 ng / mL, 5 ng / mL, 10 ng / mL, 50 ng / mL, 100 ng / mL, 200 ng / mL) was studied using the mixed standard solution. The correlation coefficient of the target alkylphenols was equal to or higher than 0.9969. The LOD and LOQ were calculated three times and ten times, respectively, based on the relationship between the regression standard deviation and the slope of the calibration curve. The LOD values in mung bean sprouts were in the range of 0.07 - 0.58 ng / g. The LOQ values in mung bean sprouts were in the range of 0.23 - 1.93 ng / g. Alkylphenol standards were added to mung bean sprouts at three different concentrations (5 ng / g, 10 ng / g, and 20 ng / g for BPA, OP, and NP, respectively); the spiked samples at the above three concentration levels (5 ng / g, 10 ng / g, and 20 ng / g) were determined in triplicate to evaluate accuracy and precision. Accuracy was calculated as the percentage of the extracted analyte (quantified using a matrix-matched calibration curve) relative to the spiked level. The accuracy of mung bean sprouts was in the range of 89.4% - 108.5%. Precision was studied by intra-day precision (repeatability) and inter-day precision (reproducibility). The intra-day and inter-day precision were in the range of 0.8% - 13.5%. During trace analysis using a complex matrix, the matrix effect (ME) was calculated based on the slope of the calibration curve. Soft signal interference was observed for all alkylphenols (-5.8% < ME < -12.4%). Due to the selectivity of the Fe3O4@rGO@PmAP composite adsorbent, the absolute value of ME was significantly lower.

[0164] Table 4 Results of method performance and validation studies

[0165]

[0166] VI. Detection Results of Alkylphenols

[0167] The contents of the target alkylphenols in three kinds of sprouts (mung bean sprouts, soybean sprouts, and peanut sprouts) were determined by the method described above in this example, and these sprouts were all purchased from the local market. The method successfully detected the alkylphenols in the sprout samples. The concentration values of the three alkylphenols are as Figure 8 shown. BPA was detected in all analyzed samples, and the average concentration range was 15.3 - 20.2 μg / kg.

[0168] In addition, the inventors found that compared with the Fe3O4@rGO composite material, the adsorption selectivity of the Fe3O4@rGO@PmAP composite material for three alkylphenols, namely 4-tert-octylphenol, nonylphenol and bisphenol A, was significantly enhanced.

[0169] In addition, the prior art reports solid phase extraction methods for analyzing the content of alkylphenols in food samples, for example, cationic gemini surfactant-resorcinol / formaldehyde resin, Fe3O4@COF and COF-GO are adsorbents for analyzing alkylphenols. Compared with other solid phase extraction methods combined with LC-MS / MS including the above methods, the LOD of alkylphenol detection in the method of the present invention is lower. The LC-MS technology used in the present invention has significantly higher detection sensitivity than HPLC detection. Fe3O4@rGO@PmAP nanocomposite materials improve the detection sensitivity of the method. In addition, the simple pretreatment method reduces the losses caused in the processing steps and ensures reliable recovery and low matrix interference. Therefore, compared with the prior art, the method has the advantages of being simple, effective and environmentally friendly, which is helpful for evaluating and monitoring alkylphenol contaminants in vegetables.

[0170] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A reduced graphene oxide composite material, characterized in that: The reduced graphene oxide composite material is Fe3O4@rGO@poly 3-aminophenol, the Fe3O4@rGO@poly 3-aminophenol uses rGO as a carrier, and the surface of the rGO is loaded with Fe3O4 and poly 3-aminophenol.

2. The method for preparing the reduced graphene oxide composite material according to claim 1, wherein: The following steps are involved: Adding divalent iron salt and trivalent iron salt to the dispersion of rGO to obtain a mixed solution, heating the mixture in the presence of ammonia water to obtain Fe3O4@rGO; polymerizing 3-aminophenol with a first initiator to obtain poly 3-aminophenol; mixing the Fe3O4@rGO and the poly 3-aminophenol, adding a second initiator, stirring, and obtaining the mixture.

3. The method according to claim 2, characterized in that The molar ratio of the divalent iron salt to the trivalent iron salt is 1:1.5-3; Optionally, the mass ratio of the rGO to the divalent iron salt is 1:10 to 40; Optionally, the mass ratio of the rGO to the ferric salt is 1:3 to 15; Optionally, the temperature of the heating reaction is 70 to 100°C; Optionally, the heating reaction time is 20 to 50 minutes.

4. The method according to claim 2, characterized in that: The molar ratio of 3-aminophenol to the first initiator is 1:0.05-2; Optionally, the polymerization reaction temperature is -4°C to 4°C; Optionally, the polymerization reaction time is 4 to 12 hours.

5. The method according to claim 2, characterized in that: The mass ratio of the Fe3O4@rGO to the poly 3-aminophenol is 1:20-60; Optionally, the mass ratio of the Fe3O4@rGO to the second initiator is 1:100-400; Optionally, the stirring temperature is -4°C to 4°C; Optionally, the stirring time is 4 to 12 hours.

6. Use of the reduced graphene oxide composite material according to claim 1 or the reduced graphene oxide composite material prepared by the method according to any one of claims 2 to 5 in enriching and detecting alkylphenols.

7. A device for enriching and detecting alkylphenols, characterized in that: The reduced graphene oxide composite material comprises the reduced graphene oxide composite material according to claim 1 or the reduced graphene oxide composite material prepared by the method according to any one of claims 2 to 5.

8. A method for detecting alkylphenols in bean sprouts, comprising sequentially performing sample treatment and solid phase microextraction on a bean sprout sample, and then performing liquid chromatography tandem mass spectrometry detection on a test solution obtained after solid phase microextraction to determine the alkylphenols in the bean sprout sample; The sample processing comprises mixing the bean sprout sample, the internal standard and acetone for extraction to obtain an extract; The solid phase microextraction comprises oscillating and extracting the extract using the reduced graphene oxide composite material according to claim 1 or the reduced graphene oxide composite material prepared by the method of any one of claims 2 to 5 to obtain the reduced graphene oxide composite material adsorbed with alkylphenol, and then oscillating and desorbing the alkylphenol adsorbed on the reduced graphene oxide composite material.

9. The method according to claim 8, characterized in that The mass volume ratio of the bean sprout sample to acetone is 1 g: 5 to 15 mL; Optionally, the extraction time is 20 to 40 minutes; Optionally, the mass ratio of the bean sprout sample to the reduced graphene oxide composite material is 1 g: 1 to 10 mg; Optionally, the oscillation extraction time is 20 to 40 minutes; Optionally, the shaking desorption is performed using ethyl acetate; Optionally, the mass volume ratio of the reduced graphene oxide composite material to ethyl acetate is 1 mg: 5 to 20 μL; Optionally, the oscillation desorption time is 20 to 40 minutes.

10. The method according to claim 8, characterized in that The liquid chromatography conditions of the liquid chromatography tandem mass spectrometry method include: Chromatographic column: Agilent ZORBAX SB-C18 column; Mobile phase A: 0.05-0.2% ammonia water; Mobile phase B: acetonitrile; Elution method: gradient elution; The procedure of the gradient elution is: 0-2 minutes, the volume fraction of mobile phase B is maintained at 55-65%, 2-3 minutes, the volume fraction of mobile phase B increases from 55-65% to 75-85%, 3-5 minutes, the volume fraction of mobile phase B is maintained at 75-85%, 5-8 minutes, the volume fraction of mobile phase B is reduced from 75-85% to 55-65%; and / or, the mass spectrometry conditions of the liquid chromatography tandem mass spectrometry include: Scanning mode: negative ionization mode; Detection method: multiple reaction monitoring mode.